2004
DOI: 10.1021/jf035332c
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate Reduces Calcium Availability in the Pads of the Prickly Pear Cactus through Formation of Calcium Oxalate Crystals

Abstract: The pads (nopales) of the prickly pear cactus are considered to be a good source of minerals and other nutrients on the basis of compositional analysis. In this study, this analysis is taken a step further by assessing the availability of selected minerals in nopales using an in vitro digestion and dialysis method. The results obtained suggest that although nopales are enriched in a number of minerals, their tissue calcium is not freely available. Microscopic analysis, energy-dispersive X-ray microanalysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
2
26
3
1
Order By: Relevance
“…In more recent studies, the mineral composition was reported to be 50, 18 -57, and 11 -17 mg/100 g dry weight for potassium, calcium, and magnesium, respectively, followed by manganese (62 -103 lg/g), iron (59 -66 lg/g), zinc (22 -27 lg/g), and copper (8 -9 lg/g) on a dry weight basis [18,27]. Again, these values should be considered approximate numbers since the mineral contents vary with species, site of cultivation, and the physiological state of the cladode tissue.…”
Section: Mineralsmentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent studies, the mineral composition was reported to be 50, 18 -57, and 11 -17 mg/100 g dry weight for potassium, calcium, and magnesium, respectively, followed by manganese (62 -103 lg/g), iron (59 -66 lg/g), zinc (22 -27 lg/g), and copper (8 -9 lg/g) on a dry weight basis [18,27]. Again, these values should be considered approximate numbers since the mineral contents vary with species, site of cultivation, and the physiological state of the cladode tissue.…”
Section: Mineralsmentioning
confidence: 99%
“…Furthermore, malic acid ranging from 95 to 985 mg/100 g fresh weight constitutes part of the free acid pool [29,35] being influenced by diurnal changes due to the CAM: the plant fixes carbon dioxide as malic acid and releases oxygen during the night to prevent water losses through transpiration. Malic acid is decarboxylated and the released carbon dioxide is converted into glucose via photosynthetic [21,27,40]. Moreover, oxalic acid has interesting inter-relationships with calcium and pectin metabolism [12,16,41].…”
Section: Organic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing ash content due to maturity might reduce quality of the cladode as fodder since ash content is negatively correlated to digestibility (Pinos-Rodríguez et al, 2006). Notwithstanding, ash is a synonym of minerals (De Alba, 1971) and its input to the feeding of cattle and humans is relevant (Mcconn & Nakata, 2004).…”
Section: Nutrimental Fodder Qualitymentioning
confidence: 99%
“…The lower intake of iron poses no concern since its bioavailability is higher due to the presence of larger amounts of vitamin C. However, calcium intake was 2.5-fold greater than the RDA levels. Since the bioavailability of calcium from Indian diets being poor due to the presence of large amounts of phytates and oxalates, which are known to reduce absorption and bioavailability of minerals [26][27][28][29][30][31][32] , the higher intakes of calcium may not have any adverse effect.…”
Section: Micronutrients Intakementioning
confidence: 99%